Proceedings of the 2020 Conference on Empirical Methods in Natural Language Processing (EMNLP) 2020
DOI: 10.18653/v1/2020.emnlp-main.542
|View full text |Cite
|
Sign up to set email alerts
|

Multi-resolution Annotations for Emoji Prediction

Abstract: Emojis are able to express various linguistic components, including emotions, sentiments, events, etc. Predicting the proper emojis associated with text provides a way to summarize the text accurately, and it has been proven to be a good auxiliary task to many Natural Language Understanding (NLU) tasks. Labels in existing emoji prediction datasets are all passage-based and are usually under the multi-class classification setting. However, in many cases, one single emoji cannot fully cover the theme of a piece … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Di↵erent studies have reported that by analyzing emoji usage, we could predict one's personality and tone, as emojis can enrich the message with additional information [46,73,29,82,40]. Several studies have analyzed emoji use, mainly focusing on how and in what kind of devices emojis are used [46,73,27], how emojis could be matched to the context in di↵erent levels and interpretations [75,31,68], and how demographic features might impact the emoji use [40]. Another thread of research investigated emoji use in instant messaging [29,99,51], and social media platforms like Twitter [82,96,87,54,38] and Facebook [93].…”
Section: Emoji Usages In Generalmentioning
confidence: 99%
“…Di↵erent studies have reported that by analyzing emoji usage, we could predict one's personality and tone, as emojis can enrich the message with additional information [46,73,29,82,40]. Several studies have analyzed emoji use, mainly focusing on how and in what kind of devices emojis are used [46,73,27], how emojis could be matched to the context in di↵erent levels and interpretations [75,31,68], and how demographic features might impact the emoji use [40]. Another thread of research investigated emoji use in instant messaging [29,99,51], and social media platforms like Twitter [82,96,87,54,38] and Facebook [93].…”
Section: Emoji Usages In Generalmentioning
confidence: 99%
“…Also, emoji prediction can be used in dialogue systems to recommend a suitable emoji (Xie et al, 2016), and using emojis in chatbot systems is effective to attract users, specifically in the conversation for mental wellbeing (Fadhil et al, 2018). Recently, Ma et al (2020) released an emoji label prediction dataset with passage-level multi-class/multi-label, and aspect-level multi-class annotations.…”
Section: Related Workmentioning
confidence: 99%